Village Fund Management for Health Programs to Reduce Stunting: A Qualitative Study of Pundungan Village, Juwiring Subdistrict, Klaten Regency - Puspaningrum, Nila Ayu (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study investigates the management of Village Fund allocations for health programs aimed at reducing stunting in Pundungan Village, Klaten Regency. In 2024, 8.7% of the Village Fund was allocated to health initiatives, resulting in a 66% reduction in stunting rates compared to 2023. The programs were implemented collaboratively by the village government, posyandu cadres, village midwives, and the local community. Research Methods: Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation. Finding/Results: The findings reveal that the success of the program was driven by targeted nutrition interventions and, crucially, by the communicative and participatory leadership of the Village Head. Conclusion: This study concludes that effective governance and community involvement are key determinants in the successful management of Village Funds for health development.